2021
DOI: 10.1038/s41467-020-20362-2
|View full text |Cite
|
Sign up to set email alerts
|

Filopodia-based contact stimulation of cell migration drives tissue morphogenesis

Abstract: Cells migrate collectively to form tissues and organs during morphogenesis. Contact inhibition of locomotion (CIL) drives collective migration by inhibiting lamellipodial protrusions at cell–cell contacts and promoting polarization at the leading edge. Here, we report a CIL-related collective cell behavior of myotubes that lack lamellipodial protrusions, but instead use filopodia to move as a cohesive cluster in a formin-dependent manner. We perform genetic, pharmacological and mechanical perturbation analyses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…The phosphorylation of MLC2 will then induce myosin activation and stress fiber contraction in cells [ 36 , 37 ]. In addition, the RhoA protein can regulate the expression of ARP2/3 to control cell filopodia and migration [ 38 , 39 ]. CDC42-induced PAK1/N-WASP activation can also regulate ARP2/3-mediated cytoskeletal remodeling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of MLC2 will then induce myosin activation and stress fiber contraction in cells [ 36 , 37 ]. In addition, the RhoA protein can regulate the expression of ARP2/3 to control cell filopodia and migration [ 38 , 39 ]. CDC42-induced PAK1/N-WASP activation can also regulate ARP2/3-mediated cytoskeletal remodeling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The actin cytoskeleton as the central hub of AJs, FAs, and NMT signaling is another interesting target to be addressed by intervention strategies for periodontal tissue regeneration [350,351]. The difference in addressing AJs or FAs on the cellular surface is that RhoA, Rac1, Cdc42 or ROCK cannot be modulated via direct interaction with a biomaterial.…”
Section: May the Force Be With You: Mt And Its Implications For Periodontal Regenerationmentioning
confidence: 99%
“…Recently, the testis myotube migration system was introduced. [ 4 ] To put it into context, some well‐established models will be summarized in this section followed by a description of the myotube system highlighting new concepts of self‐regulation in collective cell migration.…”
Section: Model Systems For Collective Cell Migrationmentioning
confidence: 99%
“…Detailed observation employing live‐cell 4D imaging of cultured pupal Drosophila testis revealed that myotubes seem likewise mesenchymal and homogeneous. [ 4 ] Before migration starts, until 28–30 h after pupae formation (APF), the anlagen of the testis and the rest of the genital tract lie separately inside the body cavity. The so‐called genital imaginal disc contains myoblasts that later build the musculature of the entire system.…”
Section: Model Systems For Collective Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation